(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Improving students’ psychomotor aspects is a key objective in the learning process, especially in natural sciences such as chemistry. This study, conducted as part of a Community Service Program (PKM), aimed to evaluate the effectiveness of laboratory-based activities in enhancing the psychomotor skills of 30 students at SMA Negeri 1 Sungai Raya. The interventions focused on acid-base titration and testing of electrolyte and non-electrolyte solutions. A quantitative experimental approach was employed, utilizing pre- and post-practicum assessments to measure changes in students’ performance. The results showed a significant improvement in psychomotor skills, with an increase of 62.38% after participating in the laboratory sessions. In addition, the effectiveness of the activities was assessed through a satisfaction questionnaire, which yielded an average score of 4.18, categorized as “satisfied.” These findings suggest that structured laboratory experiences can significantly contribute to the development of students’ practical competencies. It is recommended that educators continue to design and implement interactive, hands-on teaching strategies to foster greater student engagement in science learning.